A Coproduction Community Based Approach to Reducing Smoking Prevalence in a Local Community Setting. (30th June 2016) - McGeechan, G. J.; Woodall, D.; Anderson, L.; Wilson, L.; O'Neill, G.; Newbury-Birch, D.
Abstract : Research highlights that asset-based community development where local residents become equal partners in service development may help promote health and well-being. This paper outlines baseline results of a coproduction evaluation of an asset-based approach to improving health and well-being within a small community through promoting tobacco control. Local residents were recruited and trained as community researchers to deliver a smoking prevalence survey within their local community and became local health champions, promoting health and well-being. The results of the survey will be used to inform health promotion activities within the community. The local smoking prevalence was higher than the regional and national averages. Half of the households surveyed had at least one smoker, and 63.1% of children lived in a smoking household. Nonsmokers reported higher well-being than smokers; however, the differences were not significant. Whilst the community has a high smoking prevalence, more than half of the smokers surveyed would consider quitting. Providing smoking cessation advice in GP surgeries may help reduce smoking prevalence in this community. Work in the area could be done to reduce children's exposure to smoking in the home.